2019
DOI: 10.5173/ceju.2019.1962
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic treatment of lower pole stones: is a disposable ureteroscope preferable? Results of a prospective case-control study

Abstract: multifactorial in origin, with determinants being, among others, environmental, dietary and hereditary. The anatomy of the collecting system could be another potential risk factor. Some studies have focused on the characteristics of the inferior calyx that would be associated with a greater possibility

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
(26 reference statements)
0
14
0
Order By: Relevance
“…After the review of all the original articles, 11 studies related to this meta-analysis were identified ( Figure 1 ) [ 12 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. The characteristics of the 11 included studies are shown in Table 1 [ 12 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the review of all the original articles, 11 studies related to this meta-analysis were identified ( Figure 1 ) [ 12 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. The characteristics of the 11 included studies are shown in Table 1 [ 12 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…After the review of all the original articles, 11 studies related to this meta-analysis were identified ( Figure 1 ) [ 12 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. The characteristics of the 11 included studies are shown in Table 1 [ 12 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. All these comparative studies included patients who underwent fURS for upper ureter and renal stones with reusable or disposable flexible ureterorenoscope.…”
Section: Resultsmentioning
confidence: 99%
“…There is no consensus in the operative time between single-use FURS and reusable FURS. Although several studies have found that the single-use FURS have the advantage of shorter surgical time ( 22 24 ), a series of prospective comparative research between single-use FURS and reusable FURS have found no significant difference in mean operative time between these two surgical devices ( 7 , 17 , 18 , 25 ). As such, a prospective study with larger sample size is needed to confirm the performance of single-use and reusable FURS in terms of operative time.…”
Section: Discussionmentioning
confidence: 98%
“…A total of 287 studies were identified, out of which 28 studies were full-text reviewed and seven studies were eventually selected (16)(17)(18)(19)(20)(21)(22). The screening process is shown in Figure 1.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Data of OT were reported in six studies (16)(17)(18)(19)(20)(21) including 930 patients. The heterogeneity test results suggested that the heterogeneity among studies is high (I 2 > 50%) and a random effects model was used.…”
Section: Perioperative Outcomes Operative Timementioning
confidence: 99%